TRAINING ON HOW TO USE AND MAINTENANCE OF THE BATTERY SAFELY - Kustanto, Muh. Nurkoyim; Ilminnafik, Nasrul; Sanata, Andi (LPPM Univ. Ibn Khaldun Bogor, 2022)
Batteries are devices for storing electrical energy into chemical energy. According to the Encyclopedia Britannica, a battery is an electrochemical cell that converts chemical energy directly into electrical energy. People who use batteries have various backgrounds. especially education, ranging from uneducated people to highly educated people. So that the general public needs to know how to use and care for batteries safely. So that this service activity is so that the community understands how to use and care for safe batteries and how to properly dispose of battery waste. The impact of this service activity is that the community can understand how to use and care for safe batteries and how to properly dispose of battery waste so as not to cause environmental damage.